Prospective Evaluation of Injuries occurred during the Brazilian Soccer Championship in 2016 - Diogo Cristiano Netto; Gustavo Gonçalves Arliani; Edilson Schwansee Thiele; Monica Nunes Lima Cat; Moises Cohen; Jorge Roberto Pagura (Revista Brasileira de Ortopedia)
Abstract Objective To identify the incidence, the prevalence, the characteristics, and the possible risk factors for injuries occurring during the matches of the Brazilian Soccer Championship. Methods A prospective study was carried out to collect data on the injuries that occurred during the 2016 Brazilian Soccer Championship. Lesions were recorded by the physician responsible for each team through an online software. Results Among the 864 athletes included in the study, 231 (26.7%) of the players presented some injury during the tournament. In total, 312 injuries were recorded during the Brazilian Soccer Championship, with an average of 0.82injuries pergame. Theincidence of injuries was 24.9 injuries per 1,000 match hours. Midfielders and forwards presented, respectively, an injury risk 3.6 and 2.4 times higher than goalkeepers. Conclusion The prevalence and incidence of lesions were, respectively, 26.7% and 24.9 injuries per 1,000 match hours. The most frequently affected body segment was the lower limbs (76.3%), and the athletes acting in midfield and forward positions were themost affected. Moreover, the greater prevalence of injuries occurred in the first part of the championship.